2021
DOI: 10.3390/polym14010143
|View full text |Cite
|
Sign up to set email alerts
|

Local Variations in Carbohydrates and Matrix Lignin in Mechanically Graded Bamboo Culms

Abstract: The mechanical performance of bamboo is highly dependent on its structural arrangement and the properties of biomacromolecules within the cell wall. The relationship between carbohydrates topochemistry and gradient micromechanics of multilayered fiber along the diametric direction was visualized by combined microscopic techniques. Along the radius of bamboo culms, the concentration of xylan within the fiber sheath increased, while that of cellulose and lignin decreased gradually. At cellular level, although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…This is consistent with the literature "the difference of lignin components reflects the difference of cell functions" [10]. In particular, the variation in the modulus was mainly due to the variation in the cell wall lignification level and its composition [12]. The observed difference in the modulus of elasticity between developing and fully lignified cell walls is due to the filling of the spaces with lignin and an increase in the packing density of the cell wall during lignification [27].…”
Section: Variation Of Lignin Content Of Sw and CC In Different Agessupporting
confidence: 90%
See 2 more Smart Citations
“…This is consistent with the literature "the difference of lignin components reflects the difference of cell functions" [10]. In particular, the variation in the modulus was mainly due to the variation in the cell wall lignification level and its composition [12]. The observed difference in the modulus of elasticity between developing and fully lignified cell walls is due to the filling of the spaces with lignin and an increase in the packing density of the cell wall during lignification [27].…”
Section: Variation Of Lignin Content Of Sw and CC In Different Agessupporting
confidence: 90%
“…Along the radius bamboo culm the modulus, hardness and carbohydrates concentration also had a gradient trend [30]. The change trend of elastic modulus and hardness was positive correlation with lignin content, and the carbohydrate concentration was negative correlation with lignin content [12]. This is the relationship between the lignin distribution in micro-morphological regions and the macro properties of bamboo.…”
Section: Variation Of Lignin Content Of Sw and CC In Different Radial Locationmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, for the ber located at various position of bamboo culm, the ratio of I 1095 /I 2939 is almost constant in all the successive broad lamellae, while the ratio in the adjacent narrow layer changed obviously, with the maximum value (0.82) in the outer narrow lamellae of Bt. Our previous work has shown that the along the radius of bamboo culm the elastic modulus had a gradient decreasing trend for the broad layer of ber located at Bg, Bt and By (Jin et al 2021) in accordance with tendency of Mf orientation. Raman images by integrating over the narrow area of the C-O-C asymmetric stretching region (1083-1100 cm -1 ) are shown in Fig.…”
Section: Micro Angle Distribution At Cell Wall Layerssupporting
confidence: 56%
“…The process of obtaining XOS involves hydrolyzing the hemicellulose component using specific enzymes (endo-xylanase or β-xylosidase) or chemical methods (mild acid hydrolysis and hydrothermal pretreatment). Among these lignocellulosic biomasses, bamboo shoots (BS) are the most promising substrate for preparing XOS due to their high content of carbohydrates and low amounts of lignin [6,7]. Traditionally, BS has been recognized as a key ingredient in domestic food preparations.…”
Section: Introductionmentioning
confidence: 99%